A Constitutive Model to Predict the Elevate Temperature Flow Stress of 9Cr-1Mo Steel - Liu, Jiaojiao; Xie, Guosheng; Wan, Keyang; Liang, Xiong; Peng, Bicao (International Conference on Measuring Technology and Mechatronics Automation (Print), 2018)
Hot deformation behavior of 9Cr-1Mo ferritic steel has been studied in a wide range of temperatures (900-1200°C) and strain rates (0.01-10s-1). Using the true stress-strain data obtained from isothermal hot compression tests, a constitutive modeling has been developed. The flow stress increased with decrease of deformation temperature and increase of strain rate, which can be represented by the Zener-Hollomon parameter in an exponential equation. The contour map for flow stress at the strain of 0.8 was developed which can describe the distribution of flow stress explicitly. The influence of strain was incorporated in the developed constitutive modeling by considering effects of strain on material constants. The flow stress predicted by the constitutive model shows a satisfactory agreement with the experimental value through whole tested deformation conditions except a slight deviation for predicting the stress deformed at 900°C and 0.01s-1 and the average relative error is 5.54%.